PARTISIPASI MASYARAKAT DALAM PROGRAM KEAKSARAAN FUNGSIONAL DI DESA PONDOK BABARIS KECAMATAN SUNGAI PANDAN KABUPATEN HULU SUNGAI UTARA - Norsanti Norsanti (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2017)
Keaksaraan Fungsional Program is a government policy to reduce amount of illiteracy in Indonesia. A problem that happen in implementation of the program is society participation is still low. The reality is appeared from the low absence of society as the study citizen specially in planting and harvest season. The result of research showed that participation of society in Keaksaraan Fungsional Program in village Pondok Babaris is still limited on participation such as citizen absence while study process and lending places for studying. The factors that influence society participation in Keaksaraan Fungsional Program in village Pondok Babaris are awareness and willingness of society, the education, their economic condition, also facilities and tools of studying.